Isolation and screening antimicrobial activity of actinomycetes from marine organisms samples of the area Khanh Hoa, Vietnam - Hong Minh, Le Thi; Mai Anh, Nguyen; Thi Quyen, Vu; Thu Huyen, Vu Thi; Thi Dao, Phi; Thuy Linh, Nguyen; Mai Huong, Doan Thi; Van Cuong, Pham (Vietnam Journal of Biotechnology, 2022)
The marine environmental conditions are particularly different from terrestrial ones; recent studies have showed that marine actinomycetes might produce many novel compounds with good biological activity. The objective of this study is to isolate and screen actinomycetes strains from the marine environment with activity against pathogenic microorganisms. Fifty strains of actinomycetes were isolated from 40 samples including: sediments, sponges, soft corals, echinoderms... collected from Van Phong Bay area of Khanh Hoa province, Vietnam. The strains fermented in A+ medium and fermentation broths were extracted 5 times with ethyl acetate. The extracts were evaporated under reduced pressure to yield crude extracts. Quantitative assay was used to determine MIC (minimum inhibitory concentration) of extract against 7 test strains, including three Gram-negative bacteria (Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853, Salmonella enterica ATCC13076), three Gram-positive bacteria (Enterococcus faecalis ATCC29212, Staphylococcus aureus ATCC25923, Bacillus cereus ATCC 14579), and the yeast Candida albicans ATCC10231. The result of screening showed that: 18/50 strains have shown the antibacterial activities against at least 3 strains of tested microorganisms. In which, strains G650, G654, G657, G666, G675 inhibited three Gram-positive test microorganisms at MIC values from 8 to 64 µg/mL and C. albicans ATCC10231 with MIC values from 2 to 16 µg/mL. In addition, the two strains G657 and G666 had inhibitory effect on P. aeruginosa ATCC27853 và S. enterica ATCC13076 with MIC value 128 µg/mL. Morphological and phylogenetic investigations based on 16S rRNA gene sequences of the selected five strains showed that: strain G650 belonged to species Streptomyces ardesiacus and strain G666 high similarity to the genus Streptomyces; strain G654 showed the highest similarity to the Salinispora arenicola species; strain G657 highest similarity to the Micromonospora aurantiaca; whereas G675 belonged to the Nocardiopsis flavescens species.